Screening Of Selected Terrestrial Plants For The Control Of Cyanobacterial Growth - T Mohd Yusof, Tengku Nadiah (2017)
Efficient cyanobacterial bloom management is important because a bloom in a water body may cause problems such as unpleasant odour and taste, and most importantly, toxins production that are potentially fatal to human and animals. Previous researches have shown that various plants were able to inhibit the cyanobacterial growth. Therefore, if any wild terrestrial leaf can perform the same control, it would provide a low cost and environmental friendly alternative of cyanobacterial management. Previous researches also showed that the ability of barley straw to control cyanobacteria might likely involved complex microbial degradation.